Avaliação da presença de cianobactérias potencialmente tóxicas e microcistinas nas lagoas hipereutróficas da região da Grande Vitória, ES - Gomes, Yohanna Mayelle (2014)
One of the most relevant issues related to the euthrophication of water bodies is the proliferation of cyanobacterial strains that produce cyanotoxins. The aim of this research was to verify the presence and evaluate the potential toxicity of cyanobacteria in three lakes located in Serra-ES, Brazil. Water samples from Maringá, Juara and Jacuném lakes were collectedbetween February and December 2013. The following analyses were undertaken: water quality parameters (temperature, pH, turbidity, COD, BOD, phosphorus, nitrogen, chlorophyl a and throphic state of the water body); the detection and quantification of microcystin through High-Performance Liquid Chromatography (HPLC); and the detection of genes for the expression of phycocyanin and microcycstin through Polymerase Chain Reaction (PCR). Throughout the study these lakes presented concentrations superior to 56 μg/L for chlorophyll and 50 μg/L for phosphorus, being therefore classified as hypereuthrophic. Moreover, high levels of nitrogen, COD and BOD were detected, demonstrating that these lakes are being impacted. Microcystins were present in 56,2% (9/16) of the water samples, and in June, concentrations of 8,9 μg/L for the LR variant and 18,8 μg/L for the RR variant were respectively detected in Juara and Jacuném lakes. The gene responsible for the encoding of phycocyanin was detected in 87,5% (14/16) of the water samples, and in these same samples, the gene mcywas also detected. The results of the physicochemical analyses of the water samples and the presence of the mcygene indicate that these lakes have favourable conditions for a cyanobacterial bloom with potential toxicity. The high levels of microcystin detected in these lakes poses a risk to public health.